The State as a subject obliged to pay the procedural costs in labor and labor administrative-contentious proceedings: A space of break and entrenchment of administrative prerogatives - Huamán Ordóñez, Luis Alberto (2022)
In this paper, the author focuses on the development of the procedural costs that must be borne by the State as part of the process, with special incidence in labor and labor administrative-contentious disputes. Then, it makes a necessary tour of the notions of modern State and self-protection, in order to understand how this organization was initially abstracted from judicial control and how it was possible that it was brought to trial. To explain this scenario, the author resorts to the verdicts of the Court of Conflicts and the French Council of State, as well as the decisions of the Supreme Court of Justice of the Argentine Nation. Subsequently, it is dedicated to the study of the Code of Civil Procedure as general adjective regulation and establishes the elemental character of the theory of reparation (wrongly call of maturity) with minimal notes of the subjective theory and of the discretionary judicial moderation, for which it invokes the judicial and administrative jurisprudence to understand such procedural reception until arriving to the study of Act No. 26636 and Act No. 29497. Finally, it answers the question about whether the State, through the administration, can or should be condemned to pay costs in labor proceedings, for which it introduces some proposals, as lege ferenda, which grounds this obligation, in order for the judges to give adequate reasons for their decisions on the payment of fees.